2014
DOI: 10.1039/c4ta02851a
|View full text |Cite
|
Sign up to set email alerts
|

Fullerene-free organic solar cells with an efficiency of 3.7% based on a low-cost geometrically planar perylene diimide monomer

Abstract: A PCE of 3.7% is achieved using a low-cost monomeric PDI derivative blended with a low energy gap donor-polymer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
96
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(99 citation statements)
references
References 38 publications
(43 reference statements)
3
96
0
Order By: Relevance
“…Therefore their designs are dictated by the requirement for bulky aliphatic side chains, 40,41 or framework substituents, [42][43][44] to mitigate large-scale aggregate formation. Despite the favorable accessibility of the perylene building block, their synthesis can be demanding and low yielding, with the formation of unwanted isomers a persistent challenge limiting their synthetic scalability.…”
Section: 39mentioning
confidence: 99%
“…Therefore their designs are dictated by the requirement for bulky aliphatic side chains, 40,41 or framework substituents, [42][43][44] to mitigate large-scale aggregate formation. Despite the favorable accessibility of the perylene building block, their synthesis can be demanding and low yielding, with the formation of unwanted isomers a persistent challenge limiting their synthetic scalability.…”
Section: 39mentioning
confidence: 99%
“…10,11 Thereafter, fullerene-free solar cells and specifically perylene derivatives have seen a drastic improvement in the PCE higher than 6%. [12][13][14][15][16][17][18][19][20][21] Recently, we demonstrated that disrupting the planarity of the perylene by perpendicularly orienting two units reduces the co-facial stacking and hence improved the blend morphology. This resulted in an order of magnitude increase in the short circuit current density in OPVs made from this acceptor material.…”
mentioning
confidence: 99%
“…8b). Therefore, the PTB7-Th:SF-PDI4 blend films demonstrated higher SCLC mobilities and J SC comparing to the PTB7-Th:SF-PDI2 blend films since the face-on orientation is beneficial for vertical charge transport [73]. Based on the (010) diffraction peak (at q z~1 .59 Å À1 ) of blend films, the p-p stacking distance of the polymer backbones is calculated to be 3.95 Å.…”
Section: Resultsmentioning
confidence: 99%